Meningitis caused by Aeromonas hydrophila in Oreochromis niloticus: Proteomics and druggability of virulence factors - Fernandes, Dayanne Carla [UNESP]; Eto, Silas Fernandes; Baldassi, Amanda Cristina [UNESP]; Balbuena, Thiago Santana [UNESP]; Charlie-Silva, Ives [UNESP]; de Andrade Belo, Marco Antonio; Pizauro, João Martins [UNESP] (Elsevier, 2024)
Meningitis caused by Gram-negative bacteria is a serious public health problem, causing morbidity and mortality in both children and adults. Here, we propose a novel experimental model using Nile tilapia (Oreochromis niloticus) to study neuroinflammation. The fish were infected with Aeromonas hydrophila, and the course of infection was monitored in the peripheral blood. Septicemia was obvious in the blood, while in the brain tissue, infection of the meninges was present. The histopathological examination showed suppurative meningitis, and the cellular immune response in the brain tissue during infection was mediated by microglia. These cells were morphologically characterized and phenotyped by MHC class II markers and CD68. The increased production of TNF-α, IL-1β and iNOS supported the infiltration of these cells during the neuroinflammatory process. In the proteomic analysis of A. hydrophila isolated from brain tissue, we found chemotactic and transport proteins, proteolytic enzymes and enzymes associated with the dismutation of nitric oxide (NO), as well as motor proteins and those responsible for cell division. After characterizing the most abundant proteins during the course of infection, we investigated the druggability index of these proteins and identified promising peptide sequences as molecular targets that are similar among bacteria. Thus, these findings deepened the understanding of the pathophysiology of meningitis caused by A. hydrophila. Moreover, through the proteomics analysis, important mechanisms and pathways used by the pathogen to subvert the host response were revealed, providing insights for the development of novel antibiotics and vaccines.
Keywords: Infection; Inflammation; Microglia; Teleost; Vaccine